A Self‐Supported High‐Entropy Metallic Glass with a Nanosponge Architecture for Efficient Hydrogen Evolution under Alkaline and Acidic Conditions. (30th May 2021) - Jia, Zhe; Nomoto, Keita; Wang, Qing; Kong, Charlie; Sun, Ligang; Zhang, Lai‐Chang; Liang, Shun‐Xing; Lu, Jian; Kruzic, Jamie J.
Abstract: Developing highly efficient and durable electrocatalysts for hydrogen evolution reaction (HER) under both alkaline and acidic media is crucial for the future development of a hydrogen economy. However, state‐of‐the‐art high‐performance electrocatalysts recently developed are based on carbon carriers mediated by binding noble elements and their complicated processing methods are a major impediment to commercialization. Here, inspired by the high‐entropy alloy concept with its inherent multinary nature and using a glassy alloy design with its chemical homogeneity and tunability, we present a scalable strategy to alloy five equiatomic elements, PdPtCuNiP, into a high‐entropy metallic glass (HEMG) for HER in both alkaline and acidic conditions. Surface dealloying of the HEMG creates a nanosponge‐like architecture with nanopores and embedded nanocrystals that provides abundant active sites to achieve outstanding HER activity. The obtained overpotentials at a current density of 10 mA cm −2 are 32 and 62 mV in 1.0 m KOH and 0.5 m H2 SO4 solutions, respectively, outperforming most currently available electrocatalysts. Density functional theory reveals that a lattice distortion and the chemical complexity of the nanocrystals lead to a strong synergistic effect on the electronic structure that further stabilizes hydrogen proton adsorption/desorption. This HEMG strategy establishes a new paradigm for designing compositionally complex alloys for electrochemical reactions. Abstract : A high‐entropy metallic glass with multinary nature and chemical homogeneity is developed by a scalable metallurgical technique. Dealloying creates a nanosponge‐like architecture with embedded nanocrystals that provides abundant active sites to achieve outstanding hydrogen evolution activity in both alkaline and acidic conditions. This work will provide a roadmap for designing alloy catalysts for many years to come.